A charge amplification approach for photoacoustic tomography (PAT) with parallel acoustic delay line (PADL) arrays. (17th March 2017) - Fang, Cheng; Ustun, Arif; Cho, Young; Zou, Jun
Abstract: This paper reports the development of a new charge amplification approach for photoacoustic tomography (PAT) based on parallel acoustic delay line (PADL) arrays. By using a PADL array to create different time delays, multiple-channel PA signals can be received simultaneously with a single-element transducer followed by single-channel DAQ electronics for image reconstruction. Unlike the conventional voltage amplifiers whose output voltage drops with increasing transducer capacitance, both theoretical analysis and experimental results have shown that the charge amplification can provide almost constant transducer-amplifier gain, which is not affected by the transducer capacitance. Therefore, it allows the use of a large single-element transducer to interface many PADLs without sacrificing the SNR of each channel. This opens the possibility of using large PADL arrays to achieve PAT with a wide field of view and high lateral resolution.